Administration of dexmedetomidine in critically ill adult patients with hemorrhagic stroke: a retrospective cohort study of the MIMIC-IV database - Yuyao Zhu; Yao Xiao; Yanchao Shen; Rui Zhong; Bin Yu (Anesthesiology and Perioperative Science)
Abstract Objective Intensive care units (ICUs) widely utilize dexmedetomidine (DEX), which is a sedative agent, for its ability to maintain hemodynamic stability and provide neuroprotection. While preclinical studies have suggested that DEX improves sedation and mitigates brain injury in experimental models of intracerebral hemorrhage, its clinical effects on patients with hemorrhagic stroke (HS) remain inconclusive. This research seeks to investigate the correlation between DEX administration within the first 48 h of ICU admission and in-hospital mortality among HS patients by utilizing a large-scale database, aiming to offer evidence supporting its clinical use. Methods We conducted a retrospective cohort study based on the MIMIC-IV database. Adult patients diagnosed with hemorrhagic stroke were included and classified into a DEX group (n = 320) defined as receiving DEX within 48 h of ICU admission and a non-DEX group (n = 2432). The primary outcome was in-hospital all-cause mortality. Secondary outcomes included the incidence of hypotension, bradycardia, and ICU length of stay. Propensity score matching (PSM) was performed to minimize baseline confounding, followed by Cox proportional hazards regression and Kaplan–Meier survival analyses to assess the association between DEX administration within the first 48 h of ICU admission and in-hospital mortality. Results A total of 2,752 patients were analyzed. Before matching, Kaplan–Meier survival curves demonstrated a significantly lower in-hospital mortality in the DEX group compared with the non-DEX group (log-rank P < 0.001). Cox regression indicated that DEX administration within 48 h of ICU admission significantly reduced the risk of in-hospital death (HR = 0.56; 95% CI: 0.45–0.79; P < 0.001), and this benefit persisted after PSM adjustment. Meanwhile, patients receiving DEX had a significantly longer ICU stay than those not receiving DEX (P < 0.05), which remained consistent after PSM adjustment. No significant differences in hypotension or bradycardia were observed between the two groups. Conclusion In this retrospective cohort study of HS patients from the MIMIC-IV database, DEX administration within the first 48 h of ICU admission was associated with lower in-hospital mortality and no increased risk of hypotension or bradycardia, though it was linked to a longer ICU stay. These findings suggest that early (≤ 48 h) DEX administration may confer survival benefits for patients with hemorrhagic stroke, warranting further prospective validation.